Urban 5G NR Deployment: A Techno-Economic Case Study in Semarang - Khoirun Ni'amah; Solichah Larasati; Zein Hanni Pradana; Shinta Romadhona (Jurnal Teknik Elektro, 2025)
The deployment of 5G networks in provincial capitals such as Semarang presents challenges related to high user demand, coverage requirements, and investment costs. This research aims to evaluate the network coverage and techno-economic feasibility of 5G implementation in Semarang. Using an urban macro propagation model, two scenarios were analysed: Uplink Non-Line-of-Sight (UL-NLOS) and Downlink Non-Line-of-Sight (DL-NLOS). The UL-NLOS scenario requires 11 sites, while the DL-NLOS scenario requires 6 sites to achieve full coverage of the city. The average Synchronization Signal–Reference Signal Received Power (SS-RSRP) is −125.74 dBm, indicating sufficient signal strength. A techno-economic analysis reveals that the UL-NLOS scheme yields an NPV of IDR 292.566.473.678 with an IRR of 110.25%, while the DL-NLOS scheme yields an NPV of IDR 300.000.000.000 with an IRR of 115.38%. These results confirm that both scenarios are technically feasible and economically viable. The findings suggest that 5G deployment in Semarang can yield profitable returns, providing valuable insights for mobile operators in planning future investments.